KUALITAS LABA ATAS INTENSITAS KECURANGAN AKUNTANSI DAN MANAJEMEN LABA AKRUAL TERHADAP AGRESIVITAS PAJAK - Rahmat Irawan; Syahril Djaddang (Universitas Pakuan, 2019)
This study aims to examine the effect of accounting fraud intensity and accrual earnings management on tax aggressiveness and test earnings quality and audit quality on the accounting fraud intensity and accrual earnings management on tax aggressiveness. The testing method in this study uses multiple regression analysis. Through purposive sampling, the sample in this study amounted to 65. The data testing used structural equation model. The test results show that the intensity of accounting fraud affects tax aggressiveness, Accrual earnings management affects the tax aggressiveness, The quality of earnings strengthens the effect of accounting fraud and accrual earnings management on tax aggressiveness and Audit quality does not moderate the relationship between accounting fraud intensity and accrual earnings management with tax aggressiveness.